Electronic Driving License-based for Secure Sharing Vehicles in Wireless IoT Networks - Hariyadi, Aad; Amalia, Amalia; Wijayanti, Rieke Adriati; Rakhmania, Amalia Eka; Hidayati, Nurul; Hudiono, Hudiono (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2024)
In this paper we study electronic driving license (EDL) for secure sharing of vehicles in wireless IoT networks. The process of authentication and data transmission to the server is a very challenging problem to solve. To solve this problem, we propose the use of a wireless IoT network to overcome the transmission speed from the vehicle to the server, and the use of EDL for the driver authentication process. Two devices are installed on the vehicle side and on the server side while the wireless IoT network is used to make data transmission efficient. EDL is used to authenticate drivers who rent vehicles. When the device authentication process on the vehicle will send geographic information obtained through the global positioning system (GPS) to the server. The server will verify the user, if it matches then the server will send a command to the vehicle to be used. To run the considered system, we proposed Algorithm 1 and 2 to run the vehicle device and server, respectively. Experiment result shows the proposed system has maximum accuracy in 95.5%, packet delivery ratio 90%, delay propagation less than 60 seconds. Thus, the security of the shared vehicle will be increases.